Beta-Blockers as Therapy for Infantile Hemangiomas - Nguyen, Harrison P.; Pickrell, Brent B.; Wright, Teresa S. (Seminars in Plastic Surgery, 2014)
Infantile hemangiomas (IH) are common benign vascular tumors seen in children. Although the majority will improve spontaneously without treatment, a small subset will require therapy due to a variety of complications. Less than a decade ago, propranolol replaced corticosteroids as first-line treatment for most IH and it has proven to be a relatively safe, effective therapy. After initiation of propranolol, most hemangiomas show evidence of significant improvement relatively rapidly, often within days. Although propranolol is generally felt to have a more limited side-effect profile than systemic corticosteroids, its use has been infrequently associated with adverse events, including sleep disturbances, acrocyanosis, hypotension, bradycardia, respiratory events, and hypoglycemia. Rarely, hypoglycemic seizures have been reported, usually occurring in the setting of prolonged fasting.
Keywords: infantile hemangiomas; pediatric tumors; β-blocker; propranolol; timolol